BİRLEŞMİŞ MİLLETLER TEŞKİLATINDA YAPISAL DEĞİŞİKLİK GEREKİYOR - Atun, Yurdagül; Atun, Ata; Zort, Çağın (TURAN : stratejik arastirmalar merkezi, 2025)
Today, the restructuring of the United Nations (UN) has become the sentiment of most countries under the auspices of this organization. Implementing the necessary reforms for more comprehensive and lasting global justice and peace will give the United Nations credibility, trust, reliability, and power. Since the current political structure of our world makes it impossible for the current order of the UN to continue, it has become necessary to change the privilege provided by the veto power of the Permanent Members of the UN Security Council. The fact that these members can decide on issues that will affect the fate of other member countries has become an unfair privilege, and this situation has started to cause local problems instead of providing solutions to world problems. The vast majority of UN member states oppose this structure, which protects the interests of the five countries in question. The article examines and analyses the important changes in world politics after the end of the Cold War. It is a modest scientific study prepared to establish a more just, reliable, peaceful, and stable international order by changing the structure of the UN.